Dekonstruksi Strategi Pembelajaran IPS Terpadu Abad XXI: Analisis Kritis Efektivitas Gaya Belajar Honey & Mumford dalam Membangun Kompetensi Holistik Siswa - Nurfitriatun Nurfitriatun; Syafril Syafril; Siti Sanisah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Learning styles are believed to play an important role in shaping student competencies. This study aims to analyze the effectiveness of Honey & Mumford's learning styles in building holistic competencies in students. The focus is on integrated social studies learning in the 21st century. The independent variable (X) is holistic competence, including cognitive, affective, and psychomotor aspects. The dependent variable (Y) is the Honey & Mumford learning style, which consists of activist, reflector, theorist, and pragmatist aspects. The study uses a quantitative correlational approach with 77 eighth-grade students at SMP Negeri 5 Jonggat as subjects. Data were collected using a questionnaire with a Likert scale, based on indicators of Honey & Mumford's learning styles and holistic competencies. Analysis reveals a positive and significant relationship between learning styles and holistic competencies (r = 0.434; p < 0.001). Learning styles contribute 18.9% to the variation in students' holistic competencies. This finding underscores the importance of applying learning styles aligned with individual preferences to improve 21st-century educational outcomes. Teachers are advised to conduct diagnostic assessments to identify students' initial abilities. This enables teachers to design differentiated learning according to students' learning styles. Schools should develop policies and teacher training focused on student-centered learning. Curricula and learning resources should also be flexible. This flexibility supports diverse learning preferences and helps develop students' academic potential and character.